2019
DOI: 10.24036/107327-0934
|View full text |Cite
|
Sign up to set email alerts
|

Pembuatan Komik Literasi Informasi Untuk Meningkatkan Literasi Siswa di Perpustakaan SMA Negeri 1 Padang

Abstract: The writing of this paper aims to explain the making of information literacy comics to increase student literacy in the Public Library of Padang 1 High School. The method used in this paper is descriptive method, the data is taken through field observations and interviews with librarians and librarians, based on facts that occur in the field of Public Library 1 Padang. Based on these results it can be concluded that the making of information literacy comics can be concluded the following steps. Determine the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Mayer (2009) suggested that design is very necessary because it attracts students' interest, some experts argue that visuals can affect students' emotions (Tomita, 2018). Comics can be used as media to improve student literacy because comics present messages in the form of (design) pictures that are interesting and easy to understand by students (Ilham, 2019). Children's interest in comic books has been studied for a long time, including by Hurlock who said that regardless of the level of intelligence, almost all children like comic books, both jokes and adventures.…”
Section: Introductionmentioning
confidence: 99%
“…Mayer (2009) suggested that design is very necessary because it attracts students' interest, some experts argue that visuals can affect students' emotions (Tomita, 2018). Comics can be used as media to improve student literacy because comics present messages in the form of (design) pictures that are interesting and easy to understand by students (Ilham, 2019). Children's interest in comic books has been studied for a long time, including by Hurlock who said that regardless of the level of intelligence, almost all children like comic books, both jokes and adventures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, digital literacy is important for students to have confidence and a critical attitude in consuming information that can be justified (Silvana & Darmawan, 2018). Digital information and data processing is one of important skills in developing the ability to operate digital devices and explore digital data and information to get appropriate results (Ilham & Marlini, 2019). In addition, now the world of education is faced with many sources of information that are scattered and accepted by students, but this makes students confused in filtering the information and data obtained because not all the information that is spread can be trusted and is appropriate with the needs.…”
mentioning
confidence: 99%